2013
DOI: 10.1002/micr.22153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning curve on flap selection, re‐exploration, and salvage rates in free flaps; A retrospective analysis of 155 cases

Abstract: The purpose of this study is to report our experience and learning curve in avoiding complications at both the recipient and donor sites as well in choosing the best flap for different anatomic locations. For this purpose 155 free flaps done between October 2005 and August 2012 were retrospectively examined. Patient demographics, flap types, etiology, re-exploration indications, timing of the re-explorations, and salvage rates were documented. In the first 60 cases, our re-exploration rate was 26.7% (16 flaps)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…It is known that microvascular surgeons have better outcomes with the higher number of cases they have performed 11,12 . This has also been shown with a statistically significant reduced reexploration rate from a center’s first 60 to the following 60 flaps 13 . A study at the Boston Eye and Ear Infirmary showed an improved failure rate from 13% during the first year with 29 flaps to a 2.5% failure rate 10 years later with 81 flaps 4 .…”
Section: Discussionmentioning
confidence: 94%
“…It is known that microvascular surgeons have better outcomes with the higher number of cases they have performed 11,12 . This has also been shown with a statistically significant reduced reexploration rate from a center’s first 60 to the following 60 flaps 13 . A study at the Boston Eye and Ear Infirmary showed an improved failure rate from 13% during the first year with 29 flaps to a 2.5% failure rate 10 years later with 81 flaps 4 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have used the flap failure rate, salvage rate, and complication rate to evaluate the learning curve. However, none have used CUSUM analysis to determine the learning curve in head and neck free-flap reconstruction surgery [16][17][18][19]. In addition to operation time, we tried to define the phases by risk-adjusted CUSUM analysis for flap failure.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Furthermore, in microsurgery, efforts on implementing standardized protocols for anticoagulation or objective tools for flap monitoring can also reduce postoperative complications for free tissue transfer. 10 Partial flap loss can be avoided by standardized intraoperative application of Indocyanine-Green Fluorescence Angiography or the Continuous Video-Rate Laser Speckle Imaging, and safely allows adapting the flap design to the defect as well as to the angiosom. 11,12 Unfortunately, this formal and consistent approach does not exist for continuous microsurgical education of the PGY.…”
Section: Discussionmentioning
confidence: 99%